The government's role in industrial development and technological innovation: France's national policy towards nuclear energy development (Journal of Philosophy Culture and Political Science, 2019)
Abstract. This article attempts to answer the question, what would be the best perimeter to launch a sustainable and successful innovation policy? Policy towards nuclear energy in France is the principle focus to provide a partial answer to the question. The example of the French nuclear industry, whose creation and management pertaining to a state initiative at the end of World War Two, provides a typicalexample of a sector-based development on innovation resulting from a long term tradition of state interventionism and public initiatives, which can be described as a high tech Colbertisme. Considering those difficulties faced by such a prominent national champion in an economic milieu, it is questionable whether or not the adoption of the Lisbon Agenda in support of innovation and of its wide diffusionwas realistic. French nuclear operators within their national boundary have been characterised as quasi-monopoly for such a long period of time. However, it is questionable whether it was worthwhile for sustainable innovation, or to the contrary, it constituted mere a cumbersome obstacle constraining further marketable value creation. Pitelis’ comprehensive strategic model, – recognising governmentas an important actor as one of the determinants to sustainable value creation affecting both meso-and macro-environment at different time periods -, to some extent fills the theoretical gap in this area.Key words: French industrial policy, energy, nuclear, Colbertisme, state regulation